The Spherical Arbelos: El Arbelos Esférico - Mendieta, Javier G. (2018)
The arbelos is the geometric object constructed with three arcs of half-circumference, tangents two to two. It was studied initially by Archimedes who discovered many of its properties. Now, a generalization of the arbelos is the spherical arbelos and, with it arise the questions regarding the relationships that exist with the arbelos, its volume in relation to the spheres that constitute it, as well as the theorems related to the chain of spheres of Pappus and the spherical heart of Bankoff. The objective of this article is not to explore the properties of the arbelos, but those of the spherical arbelos; we how how two of the important properties of the arbelos can not be generalized to the spherical arbelos.